Single-cell transcriptomic analysis reveals a systemic immune dysregulation in intravenous immunoglobulin non-responsive Kawasaki disease - Feng, Chenhui; Li, Qirui; Yang, Minna; Chen, Yeshi; Zhang, Mingming; Wang, Hongmao; Li, Xiaohui (Frontiers in Immunology, 2025)
BackgroundIntravenous immunoglobulin (IVIG) has been established as the first-line treatment for Kawasaki disease (KD). However, 10%–20% of patients are unresponsive, increasing their risk of coronary artery complications.MethodsTo elucidate the pathogenesis of IVIG non-responsiveness, we performed single-cell transcriptomic profiling on 24 peripheral blood mononuclear cell (PBMC) samples from responsive and non-responsive KD patients before and after IVIG treatment. Finally, the expression of key cytokines was validated using public bulk RNA-seq data and enzyme-linked immunosorbent assay (ELISA).ResultsNon-responders exhibited elevated inflammatory cells, lymphocyte dysfunction, and a stronger inflammatory cytokine response driven by the S100A12–TLR4–MYD88 axis, initiated by Mono_CD14_CD16 cells, which was closely associated with interferon activation. Despite T/NK-cell exhaustion, cytotoxic activity was preserved. All processes appeared to be closely associated with interferon activation. Disrupted Tfh–B-cell coordination was observed alongside plasmablast enrichment. Furthermore, monocytic myeloid-derived suppressor cells (MDSCs) suppressed T-cell function and promoted inflammation. The expression levels of S100A8/A9, S100A12, TNF, TNFSF8/10, and interferon-α were consistent with the transcriptomic data.ConclusionsOur findings reveal the immune landscape in IVIG non-responsive KD and suggest potential targets for alternative therapies.